[Coconut Picker] - de S. Pinto, David (De Sola Pinto Associates, 2009)
A picture of two men climbing a coconut tree with their limbs wrapped around the trunk of the tree. A description on the back of the postcard reads "The straightest route to the freshest fruit. Jamaicans love coconut water, the most refreshing drink on a hot day. Coconut is an essential ingredient in the favourite national dish known as "Rice and Peas"." Affixed to the back of the postcard is a Jamaica 8 dollar stamp. Postcard numbered V45.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Tree climbing--Trinidad and Tobago